2012
DOI: 10.1007/s00256-012-1512-4
|View full text |Cite
|
Sign up to set email alerts
|

Femoral geometric parameters and BMD measurements by DXA in adult patients with different types of osteogenesis imperfecta

Abstract: BMD measurement in osteogenesis imperfecta patients is very critical. The combination of BMD and geometric structural measurements at the hip in osteogenesis imperfecta patients may represent an additional helpful means in estimating bone strength and fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Wekre et al [22] investigated 90 OI patients (78 of them with the milder forms OI type I and type IV) and found that only 10 % of adults with OI had osteoporotic T scores (T ≤ − 2.5). These results are consistent with a more recent study [21] where BMD was evaluated in a cohort of 30 adults with OI with different clinical severity. The authors reported that only 10 % of the patients with OI type I had a T score in the osteoporotic range (< − 2.5) at the total hip or the trochanteric region, and only 25 % had osteoporotic values at the femoral neck.…”
Section: Imaging Techniques Used To Assess Bone Mass and Matrix Minersupporting
confidence: 95%
See 3 more Smart Citations
“…Wekre et al [22] investigated 90 OI patients (78 of them with the milder forms OI type I and type IV) and found that only 10 % of adults with OI had osteoporotic T scores (T ≤ − 2.5). These results are consistent with a more recent study [21] where BMD was evaluated in a cohort of 30 adults with OI with different clinical severity. The authors reported that only 10 % of the patients with OI type I had a T score in the osteoporotic range (< − 2.5) at the total hip or the trochanteric region, and only 25 % had osteoporotic values at the femoral neck.…”
Section: Imaging Techniques Used To Assess Bone Mass and Matrix Minersupporting
confidence: 95%
“…Moreover, 40 % of patients with OI type I had a T score within normal range at the total hip and neck and 45 % at the trochanter. In contrast, in the same study, the authors reported that all individuals with OI type IV or type III had a T score of − 2.5 or below at the femoral neck and 70 % showed osteoporotic T scores at the trochanter and the total hip [21]. Studies based on pQCT measurements revealed that the volumetric BMD could be abnormally high, normal, or low, differing between radius and tibia even in the same individual [9][10][11].…”
Section: Imaging Techniques Used To Assess Bone Mass and Matrix Minermentioning
confidence: 77%
See 2 more Smart Citations
“…However, DXA measurements at the lumbar spine have to be excluded from analysis in case of fractures or severe scoliosis, which are present in about 50 % of patients with OI, as previously shown [38]. In these cases, aBMD can be assessed by DXL at the calcaneus.…”
Section: Discussionmentioning
confidence: 97%